2004
DOI: 10.1086/421394
|View full text |Cite|
|
Sign up to set email alerts
|

Diarrhea and Reduced Levels of Antiretroviral Drugs: Improvement with Glutamine or Alanyl-Glutamine in a Randomized Controlled Trial in Northeast Brazil

Abstract: The effects of therapy with glutamine and alanyl-glutamine on diarrhea and antiretroviral drug levels in patients with acquired immune deficiency syndrome (AIDS) were examined in a randomized, double-blinded, placebo-controlled study in northeast Brazil. Patients with AIDS and with diarrhea and/or wasting were randomized into 4 groups to determine the efficacy of glutamine or high- or low-dose alanyl-glutamine given for 7 days, compared with isonitrogenous glycine given to control subjects. All patients in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 27 publications
2
39
1
10
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
“…1 In Bolivia, diarrhea is the third leading cause of morbidity and mortality in children 5 years of age. 1 Diarrhea surveillance from national surveys for the country indicate an alarming rise in the diarrhea prevalence for this age group over time from 19.2% in 1998 to 31.3% in 2008. In Cochabamba, Bolivia, the site of this study, the most recent government survey from 2008 reported a diarrhea prevalence of 36.2% for children 5 years of age for the department.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, diarrheal disease may lead to intestinal malabsorption so that individuals on antiretroviral therapy (ART) are not acquiring essential nutrients and therapeutic dosages of medications. 5 Third, new mothers who are HIV-positive face a difficult choice to either breastfeed their infants and increase the risk of infecting them with the virus or provide formula or other replacement feeds with potentially unsafe water and increase the risk of diarrhea and other waterborne diseases. 6 Overall, up to16% of infants born to HIVpositive women acquire HIV from breastfeeding alone, accounting for up to 44% of all mother to child HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of detection by PCR is greater than that by microscopy, making it of great use for detection of low numbers of parasites in stool samples (Bialek et al, 2002). PCR for the detection of Cryptosporidium species, for example, has a sensitivity of 93% and a specificity of 95%, compared with 67% and 99%, respectively, for the Direct immunofluorescence assay (DFA) assay and 68% and 58%, respectively, for Enzyme Immuno Assay (EIA) (Bushen et al, 2004;Kar et al, 2011). In addition to identifying protozoa, the use of real-time PCR restriction fragment length polymorphism (RFLP) analysis can detect as few as 5 Cryptosporidium oocysts and can differentiate between 5 genotypes and, more recently, subtypes (Limor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%